Uncertainty in the economic theory of J.M. Keynes - Ospanbayev, Zh.A.; Baygisiev, M.K. (Journal of Economic Research & Business Administration, 2016)
The article is devoted to the analysis of a factor of uncertainty of the economic theory of J. M. Keynes. The factor of vagueness explains why people keep the economies in a liquid form, why investments are volatile and why by means of rate of percent it is impossible to influence on economies and to the investments. By uncertainty is defined also that fact that on extents of all history of mankind progress of economy goes slowly and falteringly. All the characters of the drama written by Keynes increasingly have vague ideas about the future and believe the possession of money of the important means allowing “to be insured”. Uncertainty also explains the fact that the atmosphere is gloomy expectations can be stored for a long time and inhibit economic activity after the goods, ser vices and investments will be available “at a reasonable price.” The feeling of uncertainty increases and decreases, in some the periods people are more sure of the future, in others – less. Answers in Keynes’s works that we are considering.